2015
DOI: 10.1177/2040622315578654
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of vascular calcification in patients with end-stage renal disease on hemodialysis: a cross-sectional observational study

Abstract: Background: This multicenter international cross-sectional observational study characterized vascular and valvular calcification burden and correlations with pulse pressure, diabetes, hypertension, and cardiovascular diseases in prevalent hemodialysis patients. Methods: We enrolled 275 consecutive adults with end-stage renal disease on maintenance hemodialysis for ⩾3 months. Coprimary endpoints were prevalences of: (1) echocardiographic calcification in mitral valve, aortic valve or mitral annulus; (2) aortoil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 44 publications
2
34
0
2
Order By: Relevance
“…27–29 In some studies, the prevalence is even higher; Kraus reported a prevalence of mild/moderate mitral valve and aortic valve calcification in 275 patients with ESRD on hemodialysis of 98.8% and 94.4%, respectively. 30 …”
Section: Left-sided Infective Endocarditis (Lsie) In Chronic Hemodialmentioning
confidence: 99%
See 1 more Smart Citation
“…27–29 In some studies, the prevalence is even higher; Kraus reported a prevalence of mild/moderate mitral valve and aortic valve calcification in 275 patients with ESRD on hemodialysis of 98.8% and 94.4%, respectively. 30 …”
Section: Left-sided Infective Endocarditis (Lsie) In Chronic Hemodialmentioning
confidence: 99%
“… 28 , 33 , 36 Other factors contribute to the development of these valvular and perivalvular abnormalities such as advanced age, male gender, ethnicity, duration of hemodialysis, smoking, diabetes, hypercholesterolemia, iron overload, peripheral vascular disease, cardiac dysrhythmia, and arterial hypertension. 30 , 37–40…”
Section: Left-sided Infective Endocarditis (Lsie) In Chronic Hemodialmentioning
confidence: 99%
“…VC prevalence is high in chronic hemodialysis (HD) patients. An observational multicentric study describes the presence of VC in 100% of studied patients (13).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] VC progresses rapidly in HD patients, and the occurrence of VC among HD patients is 70-90%. [5][6][7] The human broblast growth factor (FGF) family includes 22 members. [8] FGF23 and FGF21 are endocrine factors that structurally belong to the FGF19 subfamily, are released into circulation and exert systemic action.…”
Section: Introductionmentioning
confidence: 99%